MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING HISTORY - Mohinur Pardayeva Sobirjon qizi (Journals Park Publishing, 2022)
Today, much attention is paid to the study of the history of independent Uzbekistan is focused. It is a way for the younger generation to learn more about our history opportunities to be proud of our history and draw conclusions offers.
Keywords: innovation,; innovative educational technologies,; educational process